Identification of environmental impact hot spots in traditional food production lines - Ilja Gasan OSOJNIK ČRNIVEC; Romana MARINŠEK-LOGAR (Acta Agriculturae Slovenica)
Evaluating the environmental impact of agricultural food production systems is a relatively recent research activity and the present methods for assessing the environmental impact associated with production-consumption systems are input-output accounting, ecological footprint analysis, life cycle assessment, financial evaluation of environmental externalities, farm cost and food miles. Complete environmental impact analyses require considerable amounts of data and time and are very likely to be expensive. Preliminary identification of the most-evident environmental hot spots is beneficial in aiding the determination of the analysis scope and goal and in setting the borders of the studied system. In the present study a reconstruction of the production schemes was performed and the identification of evident environmental impact hot spots was performed expert-wise for four selected model food products (hard cooked cheese, dry-cured ham, beer and cauliflower), traditional in Europe. This preliminary hot spot identification was preformed specifically for a conceptual life cycle assessment (LCA) technique in prosecution. In our opinion, these results can also be employed as a basis for many other environmental impact assessment approaches.